A psicologia social do complexo de vira-lata: contribuições para o estudo da identidade nacional - Negreiros, Taciana Silva (2022)
The "mongrel complex" was described in 1958 by the writer and journalist Nelson Rodrigues as a national characteristic that manifests itself in the "inferiority to which Brazilians voluntarily place themselves in the face of the rest of the world.". Recent studies have shown that this is a selective phenomenon: white Brazilians favor Europeans over Brazilians (i.e., outgroup favoritism), but devalue Africans (i.e., ingroup favoritism). In the present study, we analyze the role of participants' skin color and identity factors and hypothesize that the behavior of white but not black Brazilians is influenced by a selective "mongrel complex" (SMC). We also examine the relationship between national identification and this phenomenon. In Study 1 (N = 410), we varied the skin color (White vs. Black) of a target of police violence and the cultural origin of that target (Europe vs. Brazil) and demonstrated that White participants' behavior was SMC while Black participants were ingroup favorites. Study 2 (N = 423) repeated this experimental paradigm and added a new cultural origin of the target (Latin America) to test SMC's selectivity toward a target of Latin American origin. Results showed differences in attribution of compensation to the victim of violence, with the target of European origin scoring higher than Brazilian and Latin American. Study 3 (N = 413) introduced a new paradigm to the study of SMC. The experimental situation concerned the hiring of an applicant, varying skin color (black vs. white) and cultural origin (Europe vs. Brazil vs. Latin America), in addition to analyzing the role of participants' national identity along with cultural origin. The results of this study showed the presence of a SMC in the behavior of Brazilians who valued Europeans over Brazilians; and Brazilians over Latin Americans. Contrary to what we expected, this pattern was present mainly among black participants. Discussion of these studies suggests that the SMC is consistent with the postulates of system justification theory. However, it is also possible that this is a national identity coping strategy used by Brazilians to distance themselves from their African and Native American origins.